Design optimization of supercritical carbon dioxide (s-CO2) cycles for waste heat recovery from marine engines - Hossain, Md. Jubayer; Chowdhury, Jahedul Islam; Balta-Ozkan, Nazmiye; Asfand, Faisal; Saadon, Syamimi; Imran, Muhammad (The American Society of Mechanical Engineers(ASME), 2021)
The global climate change challenge and the international commitment to reduce carbon emission can be addressed by improving energy conversion efficiency and adopting efficient waste heat recovery technologies. Supercritical carbon dioxide (s-CO2) cycles that offer a compact footprint and higher cycle efficiency are investigated in this study to utilize the waste heat of the exhaust gas from a marine diesel engine (Wärtsilä-18V50DF, 17.55 MW). Steady-state models of basic, recuperated, and reheated s-CO2 Brayton cycles are developed and optimized for network and thermal efficiency in Aspen Plus to simulate and compare their performances. Results show that the reheated cycle performs marginally better than the recuperated cycle accounting for the highest optimized network and thermal efficiency. For the reheated and recuperated cycle, the optimized network ranges 648–2860 kW and 628–2852 kW, respectively, while optimized thermal efficiency ranges are 15.2–36.3% and 14.8–35.6%, respectively. Besides, an energy efficiency improvement of 6.3% is achievable when the engine is integrated with an s-CO2 waste heat recovery system which is operated by flue gas with a temperature of 373 °C and mass flow rate of 28.2 kg/s, compared to the engine without a heat recovery system.